Using super resolution microscopy to investigate the role of actin in adenosine receptor organisation - Garlick, Evelyn (2023)
Membrane receptors are key to how cells interact with other cells and their environment. G Protein-Coupled Receptors (GPCRs) are a major drug target, with approximately a third of all FDA approved drugs acting on a GPCR [1]. The organisation of GPCRs in the cell membrane can play a key role in determining signalling responses and associated pharmacological parameters. There is significant evidence that the cortical actin skeleton can contribute to this organisation via the picket fence model. The direct contribution of actin architecture and dynamics to organisation of specific receptors requires further study. Therefore, this thesis applies a range of super-resolution microscopy techniques to investigate the role of cortical actin in the organisation of the human adenosine-A2A (A2AR) and -A2B receptors (A2BR).